Multimodal Nanoparticle for Primary Tumor Delineation and Lymphatic Metastasis Mapping in a Head‐and‐Neck Cancer Rabbit Model. Issue 14 (18th August 2015) - Muhanna, Nidal; MacDonald, Thomas D.; Chan, Harley; Jin, Cheng S.; Burgess, Laura; Cui, Liyang; Chen, Juan; Irish, Jonathan C.; Zheng, Gang
Abstract : 64 Cu‐porphysome nanoparticles enable superior delineation of neoplastic tissues, metastatic lymph nodes, and vascular drainage on head and neck cancer orthotopic rabbit model using positron emission tomography imaging. Additionally, the nanoparticles exhibit selective fluorescence activation in tumor and metastatic lymph nodes, which permits intraoperative real‐time visualization of disease tissues to precisely define surgical margins and prevents collateral damage during surgeries.